Repetitive transcranial magnetic stimulation for insomnia in patients with autism spectrum disorder: Study protocol for a randomized, double-blind, and sham-controlled clinical trial - Jiao, Jian; Tan, Lu; Zhang, Ye; Li, Taomei; Tang, Xiangdong (Frontiers in Psychiatry, 2022)
Background Insomnia is the most common comorbidity in children with autism spectrum disorder (ASD) and seriously affects their rehabilitation and prognosis. Thus, an intervention targeting insomnia in ASD seems warranted. Repetitive transcranial magnetic stimulation (rTMS), a potentially effective treatment for improving sleep quality and optimizing sleep structure, has already been demonstrated to alleviate insomnia symptoms and sleep disturbance in different neurological and neuropsychiatric conditions. This trial aims to investigate the effects of rTMS on insomnia in patients with ASD. Method This study is designed to be a double-blind, randomized, and sham-controlled trial with a target sample size of 30 participants (aged 3–13 years) diagnosed with ASD comorbid with insomnia. The intervention phase will comprise 20 sessions of rTMS or sham rTMS applied over the right dorsolateral prefrontal cortex (DLPFC) within four consecutive weeks. The effect of rTMS on insomnia and other symptoms of ASD will be investigated through home-PSG (two consecutive overnights), sleep diary, CSHQ, CARS, ABC, SRS, RBS-R, and metabolomics analysis at baseline and posttreatment. A follow-up assessment 1 month after the intervention will examine the long-term effects. Discussion The results of this study may address an important knowledge gap and may provide evidence for the use of rTMS to treat insomnia in ASD. Furthermore, it will elucidate the potential mechanism and link between sleep disorders and clinical symptoms. Clinical trial registration The study is ongoing and has been registered at the Chinese Clinical Trial Registry (ChiCTR2100049266) on 28/07/2021.